2020
DOI: 10.1111/fima.12322
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy uncertainty and momentum

Abstract: We show that a news‐based measure of economic policy uncertainty (EPU) negatively forecasts momentum. A 1‐standard‐deviation increase in EPU is associated with a 1.11% decrease in risk‐adjusted momentum returns. The predictive power of EPU is robust after controlling for previously documented economic state variables and macroeconomic uncertainty. We provide an explanation for these results from the perspective of a fund flow‐induced trading mechanism and offer direct empirical support. The literature document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 81 publications
(100 reference statements)
1
9
0
Order By: Relevance
“…Based on the above, in this paper it has been proposed to analyse the possible influence of the uncertainty related to economic policies, EPU, on the profits generated by momentum strategies. Although studies such as those by Gu et al (2019) have investigated this possible influence, the role of the economic cycle and different quantiles in this relationship have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the above, in this paper it has been proposed to analyse the possible influence of the uncertainty related to economic policies, EPU, on the profits generated by momentum strategies. Although studies such as those by Gu et al (2019) have investigated this possible influence, the role of the economic cycle and different quantiles in this relationship have not been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Works such as Addoum and Kumar (2016) propose future research to examine the influence of the political climate on the profits generated by momentum strategies, suggesting that a significant portion of those profits could be associated with political interest. Along these lines, following Lou (2012) in his proposal of the mechanism based on the flow of funds to understand the momentum effect, and Starks and Sun (2016), who show that investors’ learning about fund performance signals weakens when EPU increases, Gu et al (2019) argue that the performance-chasing mutual fund flows can lead to winning stocks exceeding losing stocks only in the state of low EPU, leading to significant profits from the momentum effect. Under this assumption, these authors found that EPU predicts the profits of the momentum effect negatively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations